RANCANG BANGUN E-ARSIP AKREDITASI SEKOLAH - Inna Nur Atika; Zulfikar -; Primaadi Airlangga (SAINTEKBU, 2018)
Problems that occur in MI Negeri Kampungbaru Nganjuk current is the length of time to search for data that is archived in the map & must open the sheet per sheet to find the desired data, the data sought sometimes incomplete and even missing data. This is because the data has not been stored in the database. The purpose of this study is to make the information system of accreditation archiving in MI Negeri Kampungbaru Nganjuk regency, where the archiving information system that was still manual to be a computerized information system.The formulation of the problem is how to design an information system of school accreditation archiving at MI Negeri Kampungbaru Nganjuk regency, and can make application program of school accreditation filing system at MI Country Kampungbaru Nganjuk regency.In the implementation phase, the system uses PHP programming language, as well as MySQL as its database.Based on the conclusions of the research results, the purpose of this program is Designing an application of an accreditation archiving system to help make it easier for schools to recover the necessary data. Keywords: archiving information system, accreditation